Implementation of deep learning strategy in islamic religious education to internalize islamic values at smk hisba buana semarang - Slamet Panuntun; Belina Hendri Saputri; Moh. Fahsin; Inas Umniyah; Inayatul Farihah; Masykur (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Islamic Religious Education (PAI) in Vocational High Schools (SMK) faces challenges in shaping students' character to excel not only in vocational competencies but also in moral and spiritual integrity. The deep learning strategy is considered effective in addressing these challenges as it emphasizes deep conceptual understanding, emotional engagement, and reflective capacity toward Islamic values. This study aims to analyze the implementation of the deep learning strategy in PAI learning and its role in internalizing Islamic values in the daily lives of SMK students. The research adopts a descriptive qualitative approach, conducted at SMK Hisba Buana Semarang, focusing on 11th-grade PAI classes with the topic